2007
DOI: 10.1157/13108224
|View full text |Cite
|
Sign up to set email alerts
|

Non-compliance with appointments amongst patients attending an Allergology Clinic, after implementation of an improvement plan

Abstract: A slight reduction in non-compliance was observed after implementing the proposals made in our previous study. In view of the high costs incurred from missed appointments, the government should finance studies to reduce this problem. The causes of non-compliance may be difficult to control, including present access to the public health service. We must be alert to and/or take preventive measures in young patients and cases of previous non-compliance. The degree of non-compliance is a quality indicator, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It must, however, be stated that females are more likely than men to be compliant with their treatment and also keep their appointments, which may in turn improve treatment outcomes. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…It must, however, be stated that females are more likely than men to be compliant with their treatment and also keep their appointments, which may in turn improve treatment outcomes. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…A further study 158 observing attendance behaviour among patients attending a Spanish allergy clinic, 3 years after setting up and launching telephone reminders for patients' first appointments, suggested that one possible reason for continued non-attendance could be related to cultural factors related to certain pathologies.…”
Section: Norms Attitudes and Understandings Regarding Condition/sympmentioning
confidence: 99%
“…Elderly patients and those with comorbid conditions such as DM and chronic kidney disease often require ACE inhibitors to manage their conditions effectively. [14][15][16][17] The JNC-8 guidelines are conservative in their approach to antihypertensive medication provision, focusing on good BP control outcomes. Regular organ function tests before initiating antihypertensive medications can reduce the risk of uncontrolled BP and adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%